2023
DOI: 10.3390/vaccines11050971
|View full text |Cite
|
Sign up to set email alerts
|

Selection Effects and COVID-19 Mortality Risk after Pfizer vs. Moderna Vaccination: Evidence from Linked Mortality and Vaccination Records

Abstract: Prior research generally finds that the Pfizer-BioNTech (BNT162b2) and Moderna (mRNA1273) COVID-19 vaccines provide similar protection against mortality, sometimes with a Moderna advantage due to slower waning. However, most comparisons do not address selection effects for those who are vaccinated and with which vaccine. We report evidence on large selection effects, and use a novel method to control for these effects. Instead of directly studying COVID-19 mortality, we study the COVID-19 excess mortality perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…However, differences between vaccines seen for primary vaccination may diminish after a booster. A U.S. study compares BNT162b2 and mRNA1273 and finds a BNT162b2/mRNA1273 odds ratio for death of 2.40 (z = 4.26) after waning for primary vaccination, but only 1.25 (insignificant, z = 0.50) after a booster dose [ 24 ]. Whether larger differences between vaccines after a booster dose would emerge over a longer time period is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, differences between vaccines seen for primary vaccination may diminish after a booster. A U.S. study compares BNT162b2 and mRNA1273 and finds a BNT162b2/mRNA1273 odds ratio for death of 2.40 (z = 4.26) after waning for primary vaccination, but only 1.25 (insignificant, z = 0.50) after a booster dose [ 24 ]. Whether larger differences between vaccines after a booster dose would emerge over a longer time period is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, test-negative designs, which were the principal designs used in the observational studies that we reviewed, suffer from healthy vaccinee bias [ 82 , 83 ], in which healthier people, who face lower background risk of severe disease, are more likely to become vaccinated or boosted. This bias can be substantial, especially for VE against hospitalization or death [ 13 , 24 ]. The implication is that many studies overestimate VE (underestimate RR).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison of different vaccines’ effectiveness provided mixed results, making it complex to draw clear conclusions. While several studies reported a higher effectiveness of mRNA-1273 compared to BNT162b2 against infection and severe COVID-19 outcomes both as a primary and booster vaccination [ 51 , 52 , 53 , 54 , 55 , 56 ], in the present cohort we observed a significantly higher protection of mRNA-1273 only against SARS-CoV-2 infections or after a single dose, and the subjects who received three or more doses of mRNA-1273 showed a higher likelihood of death, as compared to the recipients of BNT162b2 only. In contrast, we observed a greater protection conferred by heterologous booster (mixed) vaccination compared with a homologous booster with BNT162b2 only, in line with the findings of immunogenicity [ 57 ] and other population-based [ 20 , 58 , 59 ] studies.…”
Section: Discussionmentioning
confidence: 99%